PENGARUH KONTROL BUDAYA TERHADAP HARGA DAN PELAYANAN SERTA DAMPAKNYA TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Pada Perhotelan di Kota Serang) - Hakim, Lukman (JURNAL RISET AKUNTANSI TIRTAYASA, 2019)
Cultural control functions as a clear differentiator of an organization and brings a sense of identity to members of the organization itself. This study aims to determine whether cultural control, price and service are factors that influence financial performance in a service company. The theory used is the Contingensy Theory. The study was conducted in the hospitality industry in Serang City by using data samples of 63 respondents. Data analysis using SEM-PLS applied with computer media. The results of hypothesis testing show (1) There is no significant effect of cultural control on financial performance, (2) There is no significant effect of cultural control on prices, (3) Cultural control has a significant and positive effect on service, (4) Price has a significant positive effect on performance finance, and (5) Services have a significant positive effect on financial performanceKeywords: Culture Control, Price, Service and Financial Performance